Snacking Habits and Level Acceptance of Freeze-Dried Probiotic Yogurt Snacks by Children - Aini, Novia Nur; Yanti, Rini; Fibri, Dwi Larasatie Nur; Utami, Tyas; Rahayu, Endang (agriTECH, 2025)
Stunting in children is a significant problem worldwide, specifically in developing countries. One of the contributing factors to this condition is dysbiosis, characterized by an imbalance in gut microbiota and is commonly observed in affected patients. To reduce the prevalence of stunting, it is critical to provide products that are rich in protein, calcium, and probiotic. In this context, freeze-dried probiotic yogurt snacks can be used as an effective solution due to their high nutritional value, ability to preserve probiotic cell viability, and extended shelf life. Therefore, this study aims to determine snacking habits and level of acceptance of yogurt snacks among children through a sensory evaluation. The result showed that parents often considered taste, health benefits, and price when purchasing snacks. Meanwhile, children showed a high preference for freeze-dried probiotic yogurt snacks, particularly due to their appealing shape. Panelist parents also considered the products to be necessary, recommended, and an alternative to unhealthy snacks. Therefore, these products may be suitable for upper-middle-class consumers due to their higher prices and will require taste improvement to increase consumer acceptance among children.